Exercise testing and prescription - Nieman, David C.
This comprehensive text describes fitness assessment and exercise prescription concepts. Exercise testing and prescription are presented within a health-related context, with practical applications for sports nutrition, weight management, the aging process, and prevention and management of chronic diseases such as heart disease, diabetes, cancer, osteoporosis, and arthritis